Run for fun: Intrinsic motivation and physical performance - Antonio Filippin; Jan C. van Ours (Institute for the Study of Labor (IZA), 2012)
We use data from the 24-hours Belluno run which has the unique characteristic that participants are affiliated with teams and run for an hour. This allows us not only to study the individual relationship between age and performance but also to study group dynamics in terms of accessions to and separations from teams in a manner that closely resembles workers and firms when individual productivity would have been perfectly observable. From our analysis we conclude that individual performance goes down with age, although the speed-age gradient is rather flat. Group performance goes down with age as well, but interestingly a counterbalancing force emerges, namely team dynamics that are driven by performance of runners who enter and leave.
urn:nbn:de:101:1-201206146623
Keywords: J14; J24; J31; 330; age; performance; attrition; Arbeitsgruppe; Motivation; Leistungsmotivation; Professioneller Sport; Italien